FUS-mediated dysregulation of Sema5a, an autism-related gene, in FUS mice with hippocampus-dependent cognitive deficits. (11th September 2019) - Ho, Wan Yun; Chang, Jer-Cherng; Tyan, Sheue-Houy; Yen, Yi-Chun; Lim, Kenneth; Tan, Bernice Siu Yan; Ong, Jolynn; Tucker-Kellogg, Greg; Wong, Peiyan; Koo, Edward; Ling, Shuo-Chien
Abstract: Pathological fused in sarcoma (FUS) inclusions are found in 10% of patients with frontotemporal dementia and those with amyotrophic lateral sclerosis (ALS) carrying FUS mutations. Current work indicates that FUS mutations may incur gain-of-toxic functions to drive ALS pathogenesis. However, how FUS dysfunction may affect cognition remains elusive. Using a mouse model expressing wild-type human FUS mimicking the endogenous expression pattern and level within the central nervous system, we found that they developed hippocampus-mediated cognitive deficits accompanied by an age-dependent reduction in spine density and long-term potentiation in their hippocampus. However, there were no apparent FUS aggregates, nuclear envelope defects and cytosolic FUS accumulation. These suggest that these proposed pathogenic mechanisms may not be the underlying causes for the observed cognitive deficits. Unbiased transcriptomic analysis identified expression changes in a small set of genes with preferential expression in the neurons and oligodendrocyte lineage cells. Of these, we focused on Sema5a, a gene involved in axon guidance, spine dynamics, Parkinson's disease and autism spectrum disorders. Critically, FUS binds directly to Sema5a mRNA and regulates Sema5a expression in a FUS-dose-dependent manner. Taken together, our data suggest that FUS-driven Sema5a deregulation may underlie the cognitive deficits in FUS transgenic mice.